Satisfaction of Prospective Hajj Pilgrims with Pharmaceutical Services at the Outpatient Unit of Dinoyo Public Health Centers - Wijaya, Dhani; Sardinella, Asyifa Nira; Syarifuddin, Sadli; Atmaja, Ria Ramadhani Dwi; Alifah, Nabila Nur (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Health hajj pilgrims should be in istitha'ah condition to do the optimum hajj worship. Health services are needed to achieve the istitha'ah, including pharmaceutical services. Providing satisfactory pharmaceutical services could motivate prospective hajj pilgrims to constantly check their health conditions at health facilities, especially public health centers. Thus, prospective hajj pilgrims can obtain and maintain the state of istitha'ah. This study aimed to determine the level of satisfaction of prospective Hajj Pilgrims with Pharmaceutical Services at the Dinoyo Public Health Center. This descriptive observational cross-sectional study was conducted from July to August 2022 at the Dinoyo Public Health Center. The population in this study were all prospective pilgrims who received pharmaceutical services at the Dinoyo Public Health Center—a study sample set of prospective pilgrims aged 18 years and over. Prospective pilgrims who are part of the Dinoyo Public Health Center employees were excluded. A validated questionnaire was used as the study instrument, and the customer satisfaction index formula stated the percentage of satisfaction. The results showed that samples were very satisfied with pharmaceutical services at the Dinoyo Public Health Center, with a portion of satisfaction in the tangible dimensions (90.3%), reliability (96.1%), responsiveness (93.7%), empathy (95.7%), guarantee (96.8%).